Relações civis-militares e as leis de acesso a informação na América Latina e no Brasil - Rodrigues, Karina Furtado (2013)
Particularly in Latin America, a vast legacy of military regimes has contributed to the entrenchment of a culture of secrecy in governments. In most of these cases, the argument used for the coup was the defense of the homeland against the communist threat, and also motivated by a sense of duty of the armed forces to preserve the rule. In this view, they would be the most qualified ones to determine when and how to intervene in the internal political order. However, to justify military intervention in the internal political order based on a 'cleansing' of democracy is always an endeavor fraught with contradictions and serious risks to freedom. This context led scholars and authorities to rethink civil control over the military, and to redefine the armed forces’ roles. On the ongoing process of democracy consolidation, the military still holds some political and veto powers within civilian governments. The civilian control of the military in Latin America faces the lack of political incentives for civilians to be involved and specialized on the subject, since there are no observed external, either internal threats. In fact, the region has been considered as a 'peace zone', where diplomatic efforts would prevail over armed conflicts. The enactment of FOI laws opens an entirely new way of civil scrutiny – a monitory democracy, which affects directly the military autonomy and organizational culture. In the study of the emergence and strength of Freedom of Information (FOI) laws in Latin America, the civil-military relations have not been considered in depth as an influential factor. From this, we sought to trace a link between, on the one hand, the existence of FOI legislation, the date of approval of the FOI law and its general and exceptions strength, and on the other hand, the civil-military relations in Latin America. We found some suggestive links to be explored. A considerable number of countries support that the civil-military relations influence both regulation of exceptions and the time the law was passed. There is a general trend in Latin America to adopt weak FOI laws in regulating exceptions. This study provides the transparency and civil-military research agendas with various possibilities of compared case studies. It was also made an in-depth case study of Brazil, a very representative country on military influence in politics. In the discussions about the law, secrecy was the most polemic topic, and besides the military and diplomats, no other actors got deeply involved against it. It was concluded that civil-military relations in Brazil were an important and non-ignorable factor in the late approval of the FOI law in the country.